POLIS ASURANSI JIWA YANG DIGADAIKAN SEBAGAI JAMINAN PINJAMAN PADA PERUSAHAAN SEQUIS LIFE DI DENPASAR - Joni Kusuma Atmaja, Putu; Sudjana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015, 2015)
Life and human activities, the nature of the show contains many essential nature of life itself. Very nature is meant here is an impermanent nature which always accompanies life and human activity in general. Agency or institution that has the ability to take over other parties are risk insurance agency, in this case is the insurance companies. Insurance is one way that can be used by people who can assist them in the provision of financial guarantees. The purpose of this study was to determine the terms of the implementation of the lien on the company's life insurance policy Sequis Life in Denpasar and to find out how to repayment of the loan if the policyholders can not repay the loan at a specified time period. Regarding the life insurance policy can also be mortgaged as collateral to borrow money on the policy provided that the insurer has2had a cash price or cash value. Type used in this paper is an empirical legal research. Data collection techniques used are collecting secondary data and primary data. This type of approach used is collecting data from the field obtained from interviews and literature study. The conclusion of this study is that if the policyholder can not repay the loan on time period specified in the agreement is to take into account the way the insurance or reduce the amount of money that will be received by the policy holder at the time of maturity of the policy with the rest of the loan plus the flowers are not paid off. If there is any money left after deducting insurance-pemotongsn cuts are returned to policyholders. Implementation of policy and the terms of the pledge is a life insurance policy should already have a cash price and submit the original policy.
Keywords: Life Insurance, Insurance Policy, Mortgage